Design multilayer rectangular patch antenna for wireless applications / Siti Shafinaz Ali - Ali, Siti Shafinaz (2011)
The purpose of this project is to design and simulation multilayer microstrip patch antenna. Rectangular patches antenna operate at 2.45 GHz in order to satisfy the wireless standard frequency. The antenna will feed by 50 Q coaxial line. The rectangular patch antenna is designed in multilayer substrate. The designed used method of proximity coupled antenna. The effect of two layer substrate on the performance of linear polarization, patch antenna is investigated in this paper. Based on simulation result, VSWR < 2, return loss less -20dB, impedance most to 50 Q. This radiation pattern also has been investigated. The antenna design used TLY 5 and TLY 5A as a substrate. In this project proposed a simple aided design (CAD) which is computer simulation technology(CST). The project has been carried by some investigation, analysis, design, and simulation using Computer Aided Design (CAD).